BREVES ESCLARECIMENTOS SOBRE UM ESCORPIÃƒO DA AMAZÃ”NIA ð˜–ð˜±ð˜ªð˜´ð˜µð˜©ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜®ð˜¢ð˜¯ð˜¢ð˜¶ð˜¢ð˜³ð˜¦ð˜¯ð˜´ð˜ªð˜´ (Scorpiones) - Matthiesen, F. A. (REVISTA DE AGRICULTURA, 2020)
BREVES ESCLARECIMENTOS SOBRE UM ESCORPIÃƒO DA AMAZÃ”NIA ð˜–ð˜±ð˜ªð˜´ð˜µð˜©ð˜¢ð˜¤ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜®ð˜¢ð˜¯ð˜¢ð˜¶ð˜¢ð˜³ð˜¦ð˜¯ð˜´ð˜ªð˜´ (Scorpiones)